The Red Army Today - Ely, Louis Brainerd (Harrisburg The Military Service Publishing Company, 1951)
Chronicles the history of Berlin from 1936 to its fall in 1945 at the end of World War II.
Include Appendix and Index
Keywords: Berlin, Battle of, Berlin, Germany, 1945 -- World War, 1939-1945 -- German -- Germany -- History -- 1933-1945